NEGOSIASI PENDIDIKAN ISLAM DAN NEGARA PADA MASA ORDE LAMA KAJIAN HISTORIS MADRASAH DAN PESANTREN - Abdur Rohman; Shodrus Syahid; M. Bustomi; Anang Sholikhuddin (Al-Insyirah: Jurnal Pendidikan dan Konseling Islam, 2026)
This study examines the negotiation process between the state and Islamic educational institutions—particularly madrasah and pesantren—during the Old Order period (1945–1965). Employing a historical approach through library research, this study analyzes how government policies toward Islamic education were formulated and how madrasah and pesantren responded through institutional adaptation. The concept of "educational negotiation" is used as an analytical tool to examine the reciprocal relationship between the state's interest in building a national education system and the Muslim community's aspiration to preserve religious education. The findings reveal that the relationship between the state and Islamic educational institutions was not subordinative but negotiative, resulting in the formal recognition of madrasah and the modernization of pesantren as the foundation of Islamic education in Indonesia.